2005
DOI: 10.1016/j.reseneeco.2005.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Does uncertainty justify intensity emission caps?

Abstract: Environmental policies often set "relative" or "intensity" emission caps, i.e., emission limits proportional to the polluting firm's output. One of the arguments put forth in favour of relative caps is based on the uncertainty on business-as-usual output: if the firm's production level is higher than expected, so will be business-as-usual emissions, hence reaching a given level of emissions will be more costly than expected. As a consequence, it is argued, a higher emission level should be allowed if the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 12 publications
4
51
1
1
Order By: Relevance
“…As in Quirion (2005), the comparison between absolute and relative caps does not depend on uncertainty in abatement costs. In this framework it depends only on uncertainty in future BAU emissions, uncertainty in future economic output, and their correlation.…”
Section: Relative Ormentioning
confidence: 99%
See 2 more Smart Citations
“…As in Quirion (2005), the comparison between absolute and relative caps does not depend on uncertainty in abatement costs. In this framework it depends only on uncertainty in future BAU emissions, uncertainty in future economic output, and their correlation.…”
Section: Relative Ormentioning
confidence: 99%
“…As mentioned, in this framework, authors advocate for the superiority of the carbon tax (Newell and Pizer, 2003). Quirion (2005) extended this approach to indexed regulation with a stochastic analytical model featuring uncertainty in business-as-usual emissions and in the slope of the marginal abatement curve. He found that intensity targets ranked better than price instrument when uncertainty in abatement costs was high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoel and Karp 2005, Newell and Pizer 2008, Quirion 2005 or in general equilibrium models (e.g. Goulder et al 1999Dissou 2005, Jotzo and Pezzey 2007 quota and the optimal taxation are found to move procycally.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, Quirion (2005) and Newell and Pizer (2008) set out to determine the conditions under which intensity targeting ought to be preferred over fixed targets, or vice versa, by choosing the policy that maximizes the expected net benefits from abatement. Following the analytical framework in Weitzman (1974), they find that indexed quantities are likely to perform better when there is a stronger positive correlation between the index and abatement cost uncertainty, with relatively small index variance as well.…”
mentioning
confidence: 99%